Critical review of thermochemical energy storage systems based on cobalt, manganese, and copper oxides. (April 2022) - Han, Xiangyu; Wang, Liang; Ling, Haoshu; Ge, Zhiwei; Lin, Xipeng; Dai, Xingjian; Chen, Haisheng
Abstract: Thermochemical energy storage (TCES) has the advantages of high energy storage density and theoretically unlimited storage period and is a promising technology to achieve continuous operation of concentrated solar power (CSP) plants. Among the various medium- and high-temperature TCES systems, metal oxide systems have the advantages of open-loop operation, and an operating temperature range compatible with CSP plants. This review summarizes the research status of cobalt, manganese, and copper oxides and their corresponding mixed systems in detail and compares their technical characteristics. In addition, the application of perovskites to TCES are also discussed. At present, TCES is still at the laboratory scale, and numerous research gaps remain in different material forms. Therefore, further research is needed to realize its application on an industrial scale. Highlights: Metal oxide systems in powder, pellet and honeycomb forms are reviewed. The technical characteristics such as energy density and cycle life are assessed. Some prospective metal oxide systems are discussed.